Mountain rescue cardiopulmonary resuscitation: a comparison between manual and mechanical chest compressions during manikin cardio resuscitation. Issue 9 (5th May 2017) - Thomassen, Oyvind; Skaiaa, Sven Christjar; Assmuss, Jorg; Østerås, Øyvind; Heltne, Jon Kenneth; Wik, Lars; Brattebo, Guttorm
Abstract : Aim: Chest compression devices are useful during mountain rescue but may cause a delay in transport if not immediately available. The aims of this prospective observational study were to compare manual and mechanical cardiopulmonary resuscitation (CPR) during transport on a sledge connected to a snowmobile with a non-moving setting and to compare CPR quality between manual and two mechanical chest compression devices. Methods: Sixteen healthcare providers simulated four different combined CPR scenarios on a sledge in a non-moving setting and during transport and two mechanical chest compression devices during transport on the sledge. The study was conducted in May 2015 in a mountain in Norway. The primary outcome measures were compression rate (compressions per minute), compression depth in millimetres, leaning (incomplete chest wall release after compression in millimetres) and chest compression fraction (fraction of total time were compression were performed). The results were analysed by descriptive and graphical methods and paired t-tests were used to compare the differences between techniques. Results: We did not observe a significant difference between moving and non-moving conditions with respect to manual compression rate (p=0.34), compression depth (p=0.50) or leaning (p=0.92). However, both the manual compression depth (p<0.001) and the leaning (p=0.04) showed a significantly larger variance during the moving runs. Conclusion: Manual chest compression is possible on a snowmobile during transport even in challenging terrain. This experimental study shows that high-quality chest compressions and manual ventilation can be performed in an intubated patient during a short-term transportation on a sledge.